2013
DOI: 10.1016/j.chiabu.2012.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Perceived sexual control, sex-related alcohol expectancies and behavior predict substance-related sexual revictimization

Abstract: Objectives Although numerous studies have documented linkages between childhood sexual abuse (CSA) and later sexual revictimization, mechanisms underlying revictimization, particularly assaults occurring in the context of substance use, are not well-understood. Consistent with Traumagenic Dynamics theory, the present study tested a path model positing that lowered perceptions of sexual control resulting from CSA may be associated with increased sex-related alcohol expectancies and heightened likelihood of risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 34 publications
2
32
0
Order By: Relevance
“…That is, the beliefs or expectancies that victims hold regarding sexual experiences (e.g., if I have sex I will feel better) likely motivate engagement in sexual behavior. In line with this view, Walsh and colleagues (2013) found that low perceived sexual control resultant from CSA influenced college women’s sex-related alcohol expectancies, which was associated with a higher likelihood of risky sexual behavior and revictimization. Thus, one potential avenue for future research is investigating whether participants’ forecasting of hypothetical sexual behavior reliably predicts future behavior.…”
Section: Discussionmentioning
confidence: 67%
“…That is, the beliefs or expectancies that victims hold regarding sexual experiences (e.g., if I have sex I will feel better) likely motivate engagement in sexual behavior. In line with this view, Walsh and colleagues (2013) found that low perceived sexual control resultant from CSA influenced college women’s sex-related alcohol expectancies, which was associated with a higher likelihood of risky sexual behavior and revictimization. Thus, one potential avenue for future research is investigating whether participants’ forecasting of hypothetical sexual behavior reliably predicts future behavior.…”
Section: Discussionmentioning
confidence: 67%
“…These feelings of betrayal, powerlessness and stigmatization may persist into adulthood. In addition, research has shown that feelings of powerlessness can be a factor contributing to engaging in risky sexual behavior [42]. We also propose that feelings of betrayal and stigmatization that may occur due to these adverse events may contribute to mental health disorders and maladaptive behaviors, and hence, an increase in the likelihood of being diagnosed with HIV and/or an STI.…”
Section: Introductionmentioning
confidence: 92%
“…Typically, studies tackle this issue in one of two ways. One way is to create non-mutually exclusive groups (i.e., rapes characterized by both force and substance-involvement are placed in both the forcible and substance-involved groups; Walsh et al, 2013;Zinzow et al, 2010). A second, more common method largely disregards the overlap, treating them in a mutually exclusive or dichotomous manner (i.e., rapes are classified as either forcible or substance-involved, based on a researcherdefined coding hierarchy; Griffin & Read, 2012;Krebs et al, 2009;Lawyer et al, 2010;Mohler-Kuo et al, 2004;Ullman & Najdowski, 2010).…”
Section: A Non-dichotomous Conceptualization Of Rapementioning
confidence: 99%